Development of E-LKPD with Problem Based Learning (PBL) Learning Model in Informatics Subject at High School - Fauzana Azizah; Asrul Huda; Yeka Hendriyani; Fadhilah (Postgraduate, University of Mataram, 2025)
This study aims to develop and examine the validity and practicality of an Electronic Student Worksheet (E-LKPD) based on the Problem-Based Learning (PBL) model to enhance student engagement and understanding in Informatics at the secondary school level. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate) proposed by Thiagarajan, Semmel, and Semmel. The E-LKPD was validated by material and media experts and tested for practicality by students and teachers. Validation results indicated an average score of 95.15% from material experts and 96.64% from media experts, both categorized as very high. Practicality tests yielded an average of 96.28% from students and 96.84% from teachers and students combined. These findings confirm that the developed E-LKPD is highly valid and practical for use in Informatics learning. Moreover, its implementation shows potential to foster student engagement and understanding, aligning with the intended objectives of the development.